Application of Surface Acoustic Wave Sensors for Liquid Helium-4 and Helium-3 - Aoki, Y.; Wada, Y.; Sekimoto, Y.; Yamaguchi, W.; Ogino, A.; Saitoh, M.; Nomura, R.; Okuda, Y. (Journal of low temperature physics, 2004)
A surface acoustic wave (SA W) sensor can be used to determine the acoustic properties of liquid He. We applied this sensor for liquid 3He and liquid 4He. Two kinds of SA W were used in this experiment, Rayleigh-SA W and shear horizontal SA W. The damping of Rayleigh-SA W was measured in liquid 4He. The results agreed well with the reported values of the acoustic impedance, and the superfluid transition was clearly seen. The damping and the phase shift of shear horizontal SA W were measured in the normal liquid 3He. Temperature dependence of the damping and the phase shift was analyzed by the viscoelastic model, and the results were compared with the transverse acoustic impedance in the normal 3He.